Meningkatkan Power Otot Kaki Dengan Kombinasi Latihan Bunny Hop Dan Squat Jump - Siantoro, Gigih; Wiriawan, Oce; Rasyid, Muhammad Labib Siena Ar; Mohamad, Mohd Izham (Universitas Negeri Padang, 2023)
The purpose of this study was to determine the effect of a combination of bunny hop (ladder drill) and squat jump (plyometric) exercises in increasing leg muscle power. The type of research used was a quasi-experimental design with one group pretest-posttest design. The population of this study were badminton extracurricular students at SMP Negeri 1 Jogoroto, and a purposive sampling technique was used to determine the research subjects and 12 students were obtained. The research subjects were given a combination treatment of bunny hop and squat jump exercises which were carried out three days a week for six weeks. The test instrument used is jump MD, then the result of the jump height is used to calculate the power formula. The instrument is used during the pretest and posttest. The data analysis technique used was descriptive statistics, the Shapiro-Wilk normality test, and the paired sample t-test with the help of Microsoft Excel and SPSS applications. The results showed that the average value of leg muscle power during the pretest was 341.7 watts, while the posttest was 447.05 watts. The results of the Shapiro-Wilk normality test showed that the data were normally distributed (p>0.05) and the paired sample t-test showed a significance value of 0.00 (p<0.05) so the results of the study showed that the treatment given in this study could significantly increase muscle power limbs. The conclusion is that the combination of bunny hop and squat jump exercises can increase leg muscle power.